The New Campaign Finance Sourcebook - Corrado, Anthony, 1957- (Book collections on Project MUSE., 2005)
"Comprehensive exposition of federal campaign finance law and administration following the enactment, consitutional defense, and implementation of the 2002 Bipartisan Campaign Finance Reform Act (McCain-Feingold)"--Provided by publisher